2013
DOI: 10.1021/jp403766p
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Effect of in Situ Formed Nano NbH and LiH1–xFx for Improving Reversible Hydrogen Storage Properties of the Li–Mg–B–H System

Abstract: A significant improvement in hydrogenation/dehydrogenation properties of 2LiH/MgB 2 can be achieved by adding NbF 5 . The results show that the NbF 5 additive is effective for enhancing the de/hydrogenation kinetics of the Li−Mg−B−H system and reducing the desorption temperatures of MgH 2 and LiBH 4 . For the 2LiH− MgB 2 −0.03NbF 5 sample, About 9.0 wt % hydrogen capacity is obtained rapidly under cyclic conditions of rehydrogenation within 20 min at 350 °C and dehydrogenation within 20 min at 400 °C; thus, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 32 publications
3
18
0
Order By: Relevance
“…[5][6][7][8][9][10] A prototypical RHC is the combination of LiBH4 and MgH2 in a 2:1 molar ratio with a high theoretical hydrogen capacity of 11.4 wt.% based on Eq. (2), as well as a more advantageous dehydrogenation enthalpy (42 kJ mol -1 H 2 ) due to the formation of MgB 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] A prototypical RHC is the combination of LiBH4 and MgH2 in a 2:1 molar ratio with a high theoretical hydrogen capacity of 11.4 wt.% based on Eq. (2), as well as a more advantageous dehydrogenation enthalpy (42 kJ mol -1 H 2 ) due to the formation of MgB 2 .…”
Section: Introductionmentioning
confidence: 99%
“…As we have not found the commercially supplied NbH and we also failed in the successful synthesis of high-purity NbH, the effect of single NbH on the hydrogen storage property of LiBH 4 is not analyzed in this study. However, in a previous report, 57 in situ formed NbH particles in a Li−Mg−B−H system were supposed to act as "active gateways", which facilitated the diffusion of hydrogen and thence improved the kinetics. Figure 10 shows the solid-state NMR spectra of the chemical shift of B nuclei of the hydrogenation products of the LiBH 4 -0.04(Li 3 BO 3 + NbH) system as well as the pristine LiBH 4 at different states.…”
Section: Resultsmentioning
confidence: 88%
“…As we have not found the commercially supplied NbH and we also failed in the successful synthesis of high-purity NbH, the effect of single NbH on the hydrogen storage property of LiBH 4 is not analyzed in this study. However, in a previous report, in situ formed NbH particles in a Li–Mg–B–H system were supposed to act as “active gateways”, which facilitated the diffusion of hydrogen and thence improved the kinetics.…”
Section: Resultsmentioning
confidence: 90%
“…Recently, we have also investigated the effects of various fluoride additives (NbF 5 , TiF 3 , CeF 3 , LaF 3 , and FeF 3 ) on the de/rehydrogenation properties of 2LiBH 4 –MgH 2 , , in which NbF 5 additive shows the best performance on catalysis and cycling stability. Meanwhile, a fundamental insight into the transition and mechanism of NbF 5 has been revealed. , On the other hand, it has been reported that both doping an additive and hydrogen back pressure exhibit a combined effect on improving the dehydrogenation kinetics and suppressing the formation of Li 2 B 12 H 12 in the LiBH 4 –MgH 2 system . Herein, our present investigations are focused on the promotion of cycling stability and mechanism of the LiBH 4 –MgH 2 –Al system.…”
Section: Introductionmentioning
confidence: 94%
“…To obtain a good cycling property, hydrogen back pressure is needed for the complete formation of MgB 2 with a slow kinetics because of the incubation period . According to reaction , a reversible hydrogen capacity as high as 8–10 wt % of this Li–Mg–B–H system can be obtained. , It is an effective strategy that utilizes reactive hydride composites on the dehydrogenation reactions of LiBH 4 to obtain more stable phases such as metal borides and destabilize the borohydrides, enhancing the thermodynamic performance . In addition, more explorations have been conducted and more multiple composites have been demonstrated, such as NaAlH 4 –MgH 2 –LiBH 4 , NaAlH 4 –Mg­(BH 4 ) 2 , and 2NaBH 4 + MgH 2 systems.…”
Section: Introductionmentioning
confidence: 99%